An overview of selected plate and shell FE models with graphic presentation of governing relations - Radwańska, Maria (Computer Assisted Methods in Engineering and Science, 2022)
A survey of three forms (strong, weak and variational) of mathematical models is presented using expressive diagrams initiated in [3,10]. The primary and intermediate variables, governing field equations, constraint equations and variables specified by boundary conditions are components of the graphic representation of various FE (finite element) formulations. The attention is focused on linearly elastic plate element QUAD [9] for Mindlin-Reissner theory and shell elements EAS4-ANS, EAS7-ANS [1] based on CBRST (Continuum Based Resultant Shell Theory). In both cases the mixed FE models with the EAS (enhanced assumed strain) and ANS (assumed natural strain) concepts are used.